Association between neighborhood food environment and dietary diversity score among older people in Beijing, China: A cross-sectional study - Zhang, Man; Zhang, Na; Zhou, Mingzhu; Ma, Guansheng (Frontiers in Nutrition, 2022)
Objective: To examine the association between the neighborhood food environment and dietary diversity score among elderly people in China. Methods: Participants were recruited from 12 communities in Beijing, China, using a multi-stage stratified random sampling method. Participants were elderly people aged 65 to 80. A questionnaire survey was used to investigate the intake of various foods in the past three days, and their DDS was calculated. Baidu Map Application Programming Interface was used to measure the neighborhood food environments. Adjusted multiple linear regression was performed to estimate the associations. Results: 1,800 questionnaires were distributed, and the response rate was 98.6%. The valid rate was 99.4%. The mean age of the participants was 69.7 ± 4.3. The average DDS was 7.2±1.4. Convenience stores had the best access, followed by greengrocers and supermarkets. Sit-down restaurants had the nearest walking distance, Chinese fast-food restaurants had the largest number, and western fast-food restaurants had the worst access. Within 250 m, easier access to supermarkets (β=0.495, P<0.001), convenience stores (β=0.075, P=0.002) and Chinese fast-food restaurants (β=0.357, P<0.001) was associated with higher DDS; easier access to greengrocers (β=-0.475, P<0.001) and sit-down restaurants (β=-0.257, P<0.001) was associated with lower DDS. Within 500 m, more supermarkets were associated with higher DDS(β=0.341, P<0.001), while more greengrocers (β=-0.161, P<0.001) and western fast-food restaurants (β=-0.235, P<0.001) were associated with lower DDS. Within 800 m, access to supermarkets was positively associated with DDS (β=0.163, P<0.001), while access to greengrocers was negatively associated with DDS(β=-0.090, P<0.001). Within1000 m, better access to supermarkets (β=0.243, P<0.001), sit-down restaurants (β=0.018, P<0.001) and western fast-food restaurants (β=0.189, P<0.001) was associated with higher DDS; and better access to greengrocers (β=-0.112, P<0.001) and Chinese fast-food restaurants (β=-0.044, P<0.001) was associated with lower DDS. There was a negative correlation between the nearest distance to the supermarket and the DDS (β = −0.002, P<0.001), and a positive correlation between the nearest distance to the greengrocer and the DDS (β = 0.004, P<0.001). Conclusion: Supermarkets may increase the DDS among older adults in Beijing, while greengrocers may reduce the DDS. However, the current results are not strong enough to draw specific conclusions.